The economic interrelationships of tourism: a computable general equilibrium analysis - Gillham, Jonathan (2005)
This thesis investigates the economic interrelationships that tourism has in the wider economy in the context of a country that is heavily reliant on tourism revenues. More specifically, it seeks to examine the welfare, intersectoral, distributional, competitive, investment and dynamic issues relating to the tourism sector that have been under investigated in both the tourism and trade literature. These issues have been investigated empirically using Computable General Equilibrium (CGE) analysis. The thesis is set out as follows: Chapter 1 sets out the relative position of Spain in terms of its international competitors and defines the tourism sector. It also explains why CGE modelling is felt to be the most suitable approach for modelling the Spanish tourism sector for the purposes of this thesis. It also presents an overview of the planned research. Chapter 2 gives an overview of the structure and key features of the Spanish economy. It discusses the evolution of the tourism sector and how it varies between the different autonomous communities in Spain. The Spanish Tourism Satellite Account is presented and Spanish tourism policy is examined. Chapter 3 reviews the theoretical and empirical literature on CGE modelling and tourism analysis relevant to this thesis. Various types of CGE model are scrutinised and their usefulness assessed. The role of tourism in international trade is considered and the characteristics of the tourism sector that need to be embodied into a CGE model are discussed. Chapter 4 describes the core CGE model used in this thesis and the underlying equations that are associated with it. The central data set used is the Spanish input-output table for 1996. This data set is described and all subsequent input-output tables used in other chapters are amended so as to be consistent with this data set. Closure rules, elasticity parameters, solution methods and calibration methods are also discussed. Chapter 5 presents the results of the experiments carried out with the dynamic Spanish national CGE model. The core model presented in Chapter 4 has been extended to incorporate foreign direct investment and these changes are disclosed in the opening sections. Counterfactuals are designed so as to estimate the impact of foreign direct investment inflows and tourism demand shocks on the Spanish economy. Sensitivity analysis of the key exogenous parameters is also undertaken. Chapter 6 presents the results of the experiments carried out on the static regional CGE model of the regions of Spain. Input-Output tables for four of Spain's autonomous regions were obtained and integrated with the Spanish national table to create a data set which accounts for the four regions analysed and the remainder of the Spanish economy. The model presented in Chapter 4 is adapted to incorporate regional trade flows and structural differences are discussed. Counterfactuals are designed in order to investigate how regional tax policy might affect tourism flows in Spain and how tourism demand impacts on different regions in Spain. Sensitivity analysis of the key exogenous parameters is also undertaken. Chapter 7 presents the results of the experiments of the dynamic CGE model for the Canary Islands. The core model is identical to that presented in Chapter 4, except that it is applied at a sub-national rather than a national level. Counterfactuals are designed so as to take account of the issues affecting a small island economy that is heavily reliant on tourism. As before, sensitivity analysis of the key exogenous parameters is also undertaken. Chapter 8 summarises the findings of this study, highlights possibly policy implications and cites limitations of the research. Suggestions for further research are also highlighted.